Contributi per una flora vascolare di Toscana. V (247-319) - PERUZZI, LORENZO; BEDINI, GIANNI; VICIANI D. (2013)
New localities and/or confirmations concerning 73 specific and sub-specific plant taxa of Tuscan vascular flora, belonging to 56 genera and 37 families are presented: Conium, Eryngium (Apiaceae), Periploca (Apocynaceae), Mahonia (Aquifoliaceae), Asparagus, Hyacinthus (Asparagaceae), Centaurea, Crepis, Erigeron, Senecio (Asteraceae), Heliotropium, Symphytum (Boraginaceae), Lepidium, Sisymbrium (Brassicaceae), Opuntia (Cactaceae), Solenopsis (Campanulaceae), Valerianella (Caprifoliaceae), Cerastium, Sagina (Caryophyllaceae), Juniperus (Cupressaceae), Carex, Cyperus, Isolepis (Cyperaceae), Dryopteris (Dryopteridaceae), Euphorbia (Euphorbiaceae), Albizia, Dorycnopsis, Trifolium (Fabaceae), Centaurium, Cicendia (Gentianaceae), Hypericum (Hypericaceae), Gladiolus (Iridaceae),Isoetes (Isoetaceae), Juncus (Juncaceae), Salvia (Lamiaceae), Linum (Linaceae), Lindernia (Linderniaceae), Lythrum (Lythraceae), Broussonetia (Moraceae), Ophioglossum (Ophioglossaceae), Anacamptis, Neotinea, Ophrys, Serapias (Orchidaceae), Orobanche (Orobanchaceae), Oxalis (Oxalidaceae), Papaver (Papaveraceae), Bromopsis, Cenchrus, Panicum, Poa (Poaceae), Fagopyrum (Polygonaceae), Groenlandia (Potamogetonaceae), Lysimachia (Primulaceae), Solanum (Solanaceae), Verben (Verbenaceae). In the end, the conservation status of the units and eventual protection of the cited biotopes are discussed